PALAEOCLIMATIC AND PALAEOCEANOGRAPHIC EVOLUTION OF THE MEDITERRANEAN SEA OVER THE LAST 18KA - Thomopoulos, K.; Geraga, M.; Fakiris, E.; Papatheodorou, G.; Ferentinos, G. (Bulletin of the Geological Society of Greece, 2010)
he aim of the present study is the reconstruction of the palaeoclimatic and palaeoceanographic evaluation of the Mediterranean Sea over the last 18ka based on the distribution of the planktonic foraminifera species. Planktonic foraminifera species have been proven excellent indicators of the palaeoclimatic and palaeoceanographic variability. The data set of the present study consists of the variability in the abundances of planktonic foraminifera species as has been reported and published in previous studies, after the examination of marine sediments from cores selected all over the Mediterranean Sea. The evolution in the abundance of each planktonic species is examined on a time interval spacing of 1000years suggesting implications for the palaeoclimatic and palaeoceanographic evolution of the Mediterranean Sea for the same time sampling interval (1000yrs). The most pronounced results of this study suggest that: (i) the increase in surface temperature during the warm intervals always follow a decreasing trend from eastern to western areas, (ii) the eutrophication of the Mediterranean Sea in most of the time exhibits a decreasing trend from northern to southern areas, and (iii) during the Holocene two cool spells (at around 8ka and 4ka) seems that had affected the majority of the Mediterranean region.